Pierrot lunaire in Studio and in Broadcast: Sprechstimme, Tempo and Character (Journal of the Society for Musicology in Ireland, 2007)
A comparison of a recently-discovered broadcast of Pierrot lunaire with the famous 1940 commercial recording of the work, both with Arnold Schoenberg conducting performers of his circle (notably Rudolf Kolisch, Edward Steuermann and Erika Stiedry-Wagner), shows that the different contexts of the recording studio and the live broadcast, as well as other factors, had considerable influence on the performances. This article demonstrates how tempo, character and Sprechstimme contour were affected by these different contexts. Such factors caused many listeners to experience the broadcast as an excellent performance, one which was described as superior to the commercial recording. In increasing our awareness of the distinctions between live and studio recordings, a study such as this of historical performances contributes to our view of performance as a critical element in an understanding of Western art music.The article contains 18 sound examples from the original recordings, in mp3 files that may be streamed from the journal’s website: links are embedded in the full-text PDF file.